Chondrocyte Differentiation of Human Endometrial Gland-Derived MSCs in Layered Cell Sheets. (18th November 2013) - Sekine, Waki; Haraguchi, Yuji; Shimizu, Tatsuya; Yamato, Masayuki; Umezawa, Akihiro; Okano, Teruo
Abstract : Recently, regenerative medicine using engineered three-dimensional (3D) tissues has been focused. In the fields of cell therapy and regenerative medicine, mesenchymal stem cells (MSCs) are attractive autologous cell sources. While, in bioengineered tissues, a 3D environment may affect the differentiation of the stem cells, little is known regarding the effect of 3D environment on cellular differentiation. In this study, MSC differentiation in in vitro 3D tissue models was assessed by human endometrial gland-derived MSCs (hEMSCs) and cell sheet technology. hEMSC sheets were layered into cell-dense 3D tissues and were cultured on porous membranes. The tissue sections revealed that chondrocyte-like cells were found within the multilayered cell sheets even at 24 h after layering. Immunostainings of chondrospecific markers were positive within those cell sheet constructs. In addition, sulfated glycosaminoglycan accumulation within the tissues increased in proportion to the numbers of layered cell sheets. The findings suggested that a high cell density and hypoxic environment in 3D tissues by layering cell sheets might accelerate a rapid differentiation of hEMSCs into chondrocytes without the help of chondro-differentiation reagents. These tissue models using cell sheets would give new insights to stem cell differentiation in 3D environment and contribute to the future application of stem cells to cartilage regenerative therapy.